Infrastruktur Jalan Sebagai Lahan Parkir Semarang Bridge Fountain Sungai Banjir Kanal Barat (BKB) - Permata Widianingrum; Agung Budi Sardjono (RUAS, 2021)
New tourism in Semarang City raises a problem, traffic congestion. New tourism provided in Semarang City by utilizing the existing potensial is Semarang Bridge Fountain. Semarang Bridge Fountain is a dancing fountain located in Semarang City, which inaugurated end of 2018. Located on the West Canal Flood River and becomes new icon in Semarang City. The existence of Semarang Bridge Fountain affects the surrounding road infrastructure. Namely the emergence of traffic jams when the fountain attraction takes place caused by many vehicles parked on Jenderal Sudirman street. The purpose of this research to analyze road infrastructure can be used as parking lots. The method used in this research is descriptive qualitative to explain state of West Canal Flood River. The results of this research shows that parking area became one of problems that arise during event. Many people don’t know location of official parking area provided by City Government. Congestion arises because the community gathers at one point during the event and also does not know the official parking location. From the results of analysis can be concluded need for delivery of official parking location information for community, need for firmness of official parties related arrangement of parking, also the addition of facilities so that activities aren’t concentrated at one point.